2021
DOI: 10.3390/cancers13112775
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and Therapeutic Role of Angiogenic Microenvironment in Thyroid Cancer

Abstract: Thyroid cancer is the most common endocrine malignancy, with a typically favorable prognosis following standard treatments, such as surgical resection and radioiodine therapy. A subset of thyroid cancers progress to refractory/metastatic disease. Understanding how the tumor microenvironment is transformed into an angiogenic microenvironment has a role of primary importance in the aggressive behavior of these neoplasms. During tumor growth and progression, angiogenesis represents a deregulated biological proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 167 publications
(213 reference statements)
0
8
0
Order By: Relevance
“…Several experimental and clinical data suggest that other molecules may have a role in the prognostic stratification of TC patients. These include immune checkpoint factors and immune-related signature (IRS), estrogen receptors, Vitamin D, tumor angiogenic microenvironment, circular RNAs, long noncoding RNAs, and the angiotensin converting enzymes ACE and ACE2 [ 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 ]. However, all of them are awaiting validation in large case studies.…”
Section: Thyroid Cancer Patient’s Stagingmentioning
confidence: 99%
“…Several experimental and clinical data suggest that other molecules may have a role in the prognostic stratification of TC patients. These include immune checkpoint factors and immune-related signature (IRS), estrogen receptors, Vitamin D, tumor angiogenic microenvironment, circular RNAs, long noncoding RNAs, and the angiotensin converting enzymes ACE and ACE2 [ 184 , 185 , 186 , 187 , 188 , 189 , 190 , 191 , 192 , 193 , 194 ]. However, all of them are awaiting validation in large case studies.…”
Section: Thyroid Cancer Patient’s Stagingmentioning
confidence: 99%
“…Therefore, the lncRNA that recognizes EMT may be a marker for early detection of cancer recurrence ( 26 ). LncRNAs are receiving increasing attention as a class of tumor biomarkers for early screening, targeted therapy, and prognostic evaluation ( 27 ). There is mounting evidence that lncRNAs are closely associated with the recurrence of tumors ( 28 , 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of microenvironment in thyroid carcinogenesis has been clarified [ 15 ]. The components of microenvironment (extracellular matrix components (ECM) and stromal cells) surround and support cancer cells, interacting with them through cell-cell and cell-extracellular matrix interactions [ 16 ]. These are consistent with the results we obtained; through GO analysis, we concluded that the role of quercetin in PTC is enriched in processes such as response to extracellular stimulus, oxidoreductase activity, and extracellular matrix organization.…”
Section: Discussionmentioning
confidence: 99%